Peran Komunikasi Antarpribadi Orang Tua dalam Meningkatkan Prestasi Anak - Tjang, Stella; Setyanto, Yugih (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2023)
The Covid-19 outbreak has an impact on education where learning is done online. Parents get an additional role or task, namely being a companion for children in online learning. Therefore, effective communication must be established between parents and children. The author wants to know how the role of parents in improving children's achievement through interpersonal communication. Researchers use the theory of interpersonal communication according to Joseph DeVito, namely the existence of aspects of openness, empathy, support, positive attitude and similarity. Researchers conducted a qualitative method by conducting interviews with parents in this case the mother and child. In fact, interpersonal communicationplays an important role in improving children's achievement. In addition to support, openness, empathy, and a positive attitude, parents need to provide feedback or rewards during learning so that children feel valued. Wabah Covid-19 berdampak bagi pendidikan dimana pembelajaran dilakukan dengan secara online. Orang tua mendapatkan peran atau tugas tambahan yaitu menjadi pendamping anak dalam pembelajaran online. Oleh karena itu, komunikasi yang efektif harus terbangun antara orang tua dan anak. Penulis ingin mengetahui bagaimana peran orang tua dalam meningkatkan prestasi anak melalui komunikasi antarpribadi. Peneliti menggunakan teori komunikasi antarpribadi menurut Joseph DeVito yaitu adanya aspek keterbukaan, empati, dukungan, sikap positif dan kesamaan. Peneliti melakukan metode kualitatif dengan melakukan wawancara terhadap orangtua dalam hal ini ibu dan anaknya. Faktanya komunikasi antarpribadi berperan penting dalam meningkatkan prestasi anak. Selain dukungan, keterbukaan, empati, dan sikap positif, orangtua perlu memberikan timbal balik atau reward selama pembelajaran agar anak merasa dihargai.